2019
DOI: 10.1002/pen.25267
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Self‐Healing Bio‐Based Tannic Acid‐Based Methacrylates By Thermoreversible Diels–Alder Reaction

Abstract: This investigation reports the effective use of the Diels–Alder (DA) click reaction in the preparation of self‐healing bio‐based dendritic methacrylates having reactive furfuryl functionality. Bio‐based methacrylates were synthesized by modifying tannic acid with glycidyl methacrylate and furfuryl functionality was introduced by atom transfer radical polymerization with varied amount of furfuryl methacrylate monomer. The thermoreversible network was successfully achieved by DA and retro‐DA reaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“… 98 Thanks to the multiple binding sites and special topological structure of TA, the resulting epoxy thermosets demonstrated a hierarchical network structure with desirable mechanical strength and tunable functionalities, such as shock absorption, shape memory, and sustainable uses. Similar work has also been proposed by Handique et al 104 and Baruah et al , 105 which revealed that TA could potentially replace novolac resins in a green way and alleviate the health and environmental burdens of undegradable epoxy material synthesis.…”
Section: Chemical Crosslinkingsupporting
confidence: 78%
“… 98 Thanks to the multiple binding sites and special topological structure of TA, the resulting epoxy thermosets demonstrated a hierarchical network structure with desirable mechanical strength and tunable functionalities, such as shock absorption, shape memory, and sustainable uses. Similar work has also been proposed by Handique et al 104 and Baruah et al , 105 which revealed that TA could potentially replace novolac resins in a green way and alleviate the health and environmental burdens of undegradable epoxy material synthesis.…”
Section: Chemical Crosslinkingsupporting
confidence: 78%
“…The Diels-Alder reaction can be applied to various polymers. Most of all, there are many studies that apply the Diels-Alder reaction to acrylate polymer, which is widely 2 of 14 used in coating materials [22][23][24][25][26][27][28][29]. In particular, the application of graphene or modified graphene oxide to self-healing polymers not only improves their mechanical properties, but also their healing efficiency [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic covalent interactions are based on monomers that are linked through reversible connections on either a molecular or a supramolecular level. These interactions have the capacity to undergo continuous and spontaneous changes in their constitutions by reshuffling, exchange, incorporation, and decorporation of monomers or metals ligand via Diels–Alder (DA) reactions, imine-type bonds (imines, acylhydrazones, hydrazine), radical reshuffling, siloxanes, broxine equilibrium, and disulfide exchange . These bonds have been frequently used to fabricate mechanically improved self-healing polymer composites. , This is because these can integrate the robustness of covalent bonds and the reversibility of noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%